A Solution‐Processable Small Molecule Based on Benzodithiophene and Diketopyrrolopyrrole for High‐Performance Organic Solar Cells. Issue 9 (8th May 2013) - Lin, Yuze; Ma, Lanchao; Li, Yongfang; Liu, Yunqi; Zhu, Daoben; Zhan, Xiaowei
<x xml:space="preserve">Abstract</x> A linear solution‐processable small molecule (BDT‐2DPP) based on 5‐alkylthiophene‐2‐yl‐substituted benzodithiophene and diketopyrrolopyrrole is designed and synthesized. BDT‐2DPP exhibits strong and broad absorption with low band gap, low lying energy levels matching with PC61BM and high hole mobility. Solution‐processed organic solar cells based on BDT‐2DPP:PC61BM blend showed power conversion efficiencies as high as 5.79%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>